Sistema Lupo, an Educational Method from Architecture. Thinking and Learning by Doing - González Blanco, Fermín (Universidad Autonoma de Madrid, 2017)
Sistema Lupo is a didactic method born from architecture. In this text are synthesized the methodologies and sources followed. Together they form a hybrid philosophy,where social constructivism,objectivism and even philosophical materialism are intermingled. Lupo is to think and to do,it is learning by doing,it is thinking with hands. It is an active pedagogical experience based on the constructive and mental act where building blocks of different materials and sizes constitute a fundamental tool on which a network of knowledge and experiences,that can make us travel from the object to the city,from the avant-garde to tradition or from abstraction to figuration. © 2017 The Author(s).
[Sistema Lupo, um Método Educativo a partir da Arquitetura. Pensar e Aprender Fazendo]
[Sistema Lupo, un Método Educativo desde la Arquitectura. Pensar y Aprender Haciendo]
Keywords: 62 Ciencias de las Artes y las Letras::6201 Arquitectura; ODS 11 - Ciudades y comunidades sostenibles